Inovasi Rompi Medis untuk Fisioterapis Sepakbola Berbasis Tactical Vest - Mochammad Aldiansyah , Putra; Darwin Yuwono , Riyanto; Yosef Richo , Adrianto; Erstiawan, Martinus Sony (CandraRupa : Journal of Art, Design, and Media, 2025)
This study focuses on the development of a tactical vest design specifically tailored for football physiotherapists, integrating an ergonomic and functional bag element. The background of this research arises from the necessity for physiotherapists to handle player injuries quickly and efficiently, requiring an innovative solution in the form of a multifunctional medical vest. The primary issue addressed is the limited accessibility of medical equipment when using conventional bags such as sling bags or waist bags, which can hinder the mobility and effectiveness of physiotherapists on the field. Therefore, this research aims to design a tactical vest with an optimized pocket layout, durable materials, and a storage system that facilitates quick access to medical tools. The research employs a qualitative descriptive method with an experimental approach. Data were collected through field observations, interviews with physiotherapists from the Persebaya Surabaya football team, and literature analysis on ergonomic design, materials, and pocket configurations. The design process follows the input-process-output (IPO) approach, encompassing design exploration, material selection, and production simulation. The findings reveal that the tactical vest design achieves a balance between aesthetics and functionality. The use of 1680D polyester has been proven to provide high resistance to abrasion and weather conditions, while polyfoam enhances user comfort by offering additional padding. The ergonomic design, based on anthropometry, allows greater mobility, while the strategic pocket configuration facilitates quick access to medical equipment. From an economic perspective, production cost estimates indicate that the vest has a competitive selling price with significant market potential. In conclusion, this tactical vest can serve as an innovative solution for physiotherapists to handle football player injuries efficiently and effectively. Further development may include exploring lighter materials and optimizing the design to enhance the product’s competitiveness in the sports industry market.